Fracture History in Osteoporosis: Risk Factors and its Effect on Quality of Life - AKYÜZ, GÜLSEREN DERYA; LÜLECİ, NİMET EMEL (AVES, 2015)
Background: Fractures are one of the main outcomes in osteoporosis and have an important effect on the general health status. Aims: The purpose of this study was to determine the effect of major fracture history on quality of life. We also investigated the important risk factors and their effect on bone mineral density and fracture history. Study Design: Cross-sectional study. Methods: We recruited 105 patients who were admitted to an osteoporosis outpatient clinic. Medical history, family history, calcium intake, physical activity level and biochemical tests were evaluated. Lumbar spine and femur neck bone mineral density were measured. The Qualeffo-41 questionnaire was also used for evaluating quality of life. Results: The average age of the 105 patients included in the study was 56.04 +/- 13.73 and 89% of them were post-menopausal women. The average body mass index was 26.84 +/- 5.99, which means that the women were overweight. Also, 48.5% of the patients were diagnosed with osteoporosis and 51.5% of them were diagnosed as low bone density. A total of 34 patients had a fracture history with minor trauma and some of the patients had more than one fracture (12 ankle and foot, 10 forearm, 9 vertebral, 4 hand, 3 hip, 2 rib, 1 tibial). When the patients with and without fracture history were compared, the mean Qualeffo-41 score in patients with fracture was 43.85 +/- 2.57 and in the non-fracture group was 36.27 +/- 2.01. Conclusion: Forearm, ankle and foot fractures can be commonly seen in osteoporosis patients with fracture history. We suggest that it is important to recognise osteoporosis prior to first fracture and disease-specific quality of life assessment should be done.
Keywords: Fracture; Qualeffo-41; post-menopausal women; POSTMENOPAUSAL WOMEN; VERTEBRAL FRACTURES; HEALTH; DENSITY; CALCIUM; MEN